Reconceptualizing Sustainability through Islamic Legal Philosophy: Maqāṣid al-Sharīʿah, Environmental Ethics, and Contemporary Governance - Labeeb Ahmed Bsoul; Mutasim Al Deaibes; Layan Hesham Herzalla Herzalla (Yayasan Insan Cendekia Nusantara, 2026)
Research Background: This study addresses the growing global environmental crisis by critically examining the ethical limitations of dominant sustainability paradigms, which often neglect deeper moral and metaphysical foundations. Methods: Using a normative-analytical and comparative approach, the research integrates textual analysis of Islamic sources—Qur’an, Sunnah, and classical jurisprudence—with contemporary sustainability theories such as ecological economics and the circular economy. The study focuses on the foundational Islamic principles of tawḥīd (unity), khilāfah (stewardship), and mīzān (balance), alongside the juridical framework of maqāṣid al-sharīʿah. Key Findings: The findings demonstrate that Islamic legal philosophy offers a coherent and integrative sustainability model that unites metaphysics, ethics, and law. Importantly, the study advances the extension of maqāṣid al-sharīʿah to include environmental preservation (ḥifẓ al-bīʾah) as a core objective. This framework not only aligns with contemporary environmental concerns but also provides a stronger moral and legal foundation for governance. Contribution: The study contributes to sustainability discourse by positioning Islamic jurisprudence as a globally relevant paradigm capable of enriching and restructuring existing models. Conclusion: Islamic legal philosophy presents an ethically grounded and operational framework that supports long-term, just, and holistic environmental governance.